Perceptions of women and their partners on postabortion intrauterine contraception: A qualitative study in central Uganda - Herbert Kayiga; Emelie Looft-Trägårdh; Othman Kakaire; Nazarius Mbona Tumwesigye; Musa Sekikubo; Joseph Rujumba; Josaphat Byamugisha; Kristina Gemzell-Danielsson (PLoS ONE, 2025)
Background The uptake of intrauterine devices (IUDs) has stalled below two percent among married Ugandan women. We explored the perceptions of women and their partners on the utilization of postabortion IUDs after medical management of incomplete abortions in central Uganda. Methods Between August 2022 and May 2023, using a semi-structured interview guide, fifteen in-depth interviews were conducted among Ugandan women and their partners at five public facilities on their perceptions in regards to postabortion IUDs. Using inductive content analysis, themes and subthemes were generated. Results Three themes emerged: 1) perceived women’s and their partners’ barriers in accessing postabortion IUDs such as myths and misconceptions on IUDs, spouse refusal, IUD related side effects. 2) women’s and their partners’ experiences while using postabortion IUDs such as increased lubrication, freedom from prior contraceptive side effects, assurance of early return to fertility after IUD removal, menstrual irregularities and abdominal pain following IUD insertion. 3) motivators and recommendations to the uptake of IUDs such as peer influence, client-healthcare provider relationship, spousal approval of IUDs and community sensitization on IUDs using social media platforms. Conclusion Understanding the socio-cultural context of women and their partners, is pivotal in the uptake of postabortion IUDs. Healthcare providers ought to provide evidence-based counselling to demystify individual and community misconceptions on IUD use. Male partner involvement, the assurance of early return to fertility after IUD removal, user champions, and social media platforms can enhance the uptake of postabortion IUDs.